THE INCIDENCE OF AMOEBIASIS IN THE STATE OF AMAZON - Mattos da Silva Júnior , Roberto; Silva Silveira, Jânio (Health and Society, 2023)
The most common infections in humans are caused by intestinal parasites. In Brazil, parasitic infections are a major public health problems. These infestation levels may be related to several factors such as climate, social and economic conditions and the characteristics of the parasites. In the Brazilian Amazon a few studies to determine the prevalence of intestinal parasitic infections such as amebiasis. Therefore, this study was conducted in order to examine the occurrence of amebiasis during the flood in Manaus. Amebiasis is the second leading cause of death by parasite worldwide. Among the environmental factors related to infection by Entamoeba histolytica, the variables income and possess significant source of water, suggesting that the high prevalence may be associated with poor economic conditions and sanitary living populations. The highest incidence of the parasite E. histolytica is related to the absence of regular hygiene habits such as simply washing hands before meals and after using the toilet. Furthermore, in order to health education of children and relatives can contribute to the acquisition of healthy habits avoiding generally parasitosis. We conclude that the prevalence of amoebiasis in this population, is allied to poor sanitation conditions and certain habits inappropriate constituting a worrying public health.